Absence of ULK1 decreases AMPK activity in the kidney, leading to chronic kidney disease progression. (9th November 2022) - Yanagi, Tomoki; Kikuchi, Hiroaki; Susa, Koichiro; Takahashi, Naohiro; Bamba, Hiroki; Suzuki, Takefumi; Nakano, Yuta; Fujiki, Tamami; Mori, Yutaro; Ando, Fumiaki; Mandai, Shintaro; Mori, Takayasu; et al.
Abstract: AMP‐activated protein kinase (AMPK) inactivation in chronic kidney disease (CKD) leads to energy status deterioration in the kidney, constituting the vicious cycle of CKD exacerbation. Unc‐51‐like kinase 1 (ULK1) is considered a downstream molecule of AMPK; however, it was recently reported that the activity of AMPK could be regulated by ULK1 conversely. We demonstrated that AMPK and ULK1 activities were decreased in the kidneys of CKD mice. However, whether and how ULK1 is involved in the underlying mechanism of CKD exacerbation remains unknown. In this study, we investigated the ULK1 involvement in CKD, using ULK1 knockout mice. The CKD model of Ulk1 −/− mice exhibited significantly exacerbated renal function and worsening renal fibrosis. In the kidneys of the CKD model of Ulk1 −/− mice, reduced AMPK and its downstream β‐oxidation could be observed, leading to an energy deficit of increased AMP/ATP ratio. In addition, AMPK signaling in the kidney was reduced in control Ulk1 −/− mice with normal renal function compared to control wild‐type mice, suggesting that ULK1 deficiency suppressed AMPK activity in the kidney. This study is the first to present ULK1 as a novel therapeutic target for CKD treatment, which regulates AMPK activity in the kidney. Abstract : The absence of Unc‐51‐like kinase 1 (ULK1) leads to AMP‐activated protein kinase (AMPK) inactivation and energy failure in chronic kidney disease (CKD) kidney, causing a vicious cycle of CKD progression.